Identifying Components of Effective Police Training Through Factor Analysis - Mihardja, Soma; Pramono, Suwito Eko; Yulianto, Arief; Arief, Ulfah Mediaty (Universitas Negeri Semarang, 2024)
This paper explores the critical elements contributing to the effectiveness of organizational training programs, particularly for police. Key factors include the relevance of training content to police job roles, the clarity and simplicity of the material, and the use of interactive methods such as simulations and role-playing. The research employs a quantitative approach using factor analysis. The respondents are police officers who have already undergone training, with 114 participants involved in the study. Data analysis was conducted using SPSS. The results emphasize the role of trainers, highlighting the importance of their subject matter expertise, continuous professional development, and adaptability to diverse learning styles. The research indicates that relevant and engaging training significantly enhances employee productivity, job satisfaction, and retention. By integrating these elements, organizations can design training programs that improve police performance and contribute to overall organizational success.